PENGARUH KECERDASAN EMOSIONAL, KECERDASAN INTELEKTUAL, KECERDASAN SPIRITUAL, KECERDASAN SOSIAL TERHADAP PEMAHAMAN AKUNTANSI - Catur Widatik, Rispantyo & Djoko Kristianto (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2016)
The purpose of this research is to analyzed the effect of emotional quotient, intellectual quotient, spiritual quotient, social quotient on the understanding of accountantcy concept both in partial and simultan. Research methods using empirical studies, the data type of the data being used is qualitative and quantitative data, the sources data used the data of primary and secondary. The data were analyzed by using questionare. The data were analyzed by validity and reliability. The technique of analyzing data using assumption classic test, analyzing of multiple linear regression analysis, F test, t test, determination coefisien test. The result of the study indicated: 1) The variable of intellectual quotient and social quotient had an effect of accountancy concept. 2) The variable of emotional quotient and spiritual quotient are not effected of accountancy concept. The result of F test the study indicated that that the emotional quotient, intellectual quotient, spiritual quotient, social quotient on the understanding of accountantcy concept.Keywords: emotional quotient, intellectual quotient, spiritual quotient, social quotient on the understanding of accountantcy concept.